La biblioteca escolar: un reto educativo - Nieto Formariz, Gerardo (Revista General de Información y Documentación, 2003)
The school library may come to be fundamental to the success of the school. In addition to the traditional reading and loans service, this project intends both to use the library as a learning resource and to address the students’ individual needs. One of the specific functions is to develop the students’ abilities in searching for information and in research projects. For the library to be instrumental ¡to the school’s success it should be integrated into the Curriculum Project and adequately staffed and equipped.